Diurnal and seasonal coupling of conifer sap flow and vapour pressure deficit across topoclimatic gradients in a subalpine catchment. Issue 7 (3rd July 2018) - Looker, Nathaniel; Martin, Justin; Hoylman, Zachary; Jencso, Kelsey; Hu, Jia
Abstract: The hydroclimatic controls on transpiration often follow hillslope‐ or catchment‐scale topography in water‐limited ecosystems; however, rates of transpiration may deviate from these patterns due to microtopographic variation in environmental conditions or physiology. Here, we assessed the microtopographic effects on water use of five conifer species within four subcatchments in western Montana along a water availability gradient that was driven by aspect and elevation. To infer physiological processes at both diurnal and seasonal time scales, we analysed the relationship between sap velocity, V s, and vapour pressure deficit, D, using instantaneous (half‐hourly) and aggregated (daily mean) values of V s and D . Both within and across species, daily mean V s was more tightly coupled to D at higher elevation sites (1, 720 m), whereas trees 350 m lower in elevation became decoupled from D as snowmelt‐derived soil moisture declined. At the diurnal scale, we found that the degree of decoupling of V s from D during soil moisture deficits decreased when a time lag between V s and D was considered. Additionally, contrary to the common inference of plant hydraulic capacitance based on V s lagging behind D at the diurnal scale, half‐hourly V s tended to lead D in three of the five conifer species we studied. Predawn and midday branch water potential measurements provided additional evidence that topography influenced plant water status. These results suggest that improved understanding of soil–vegetation–atmosphere coupling in mountainous terrain requires further inquiry into the spatial variability of plant hydraulic regulation.